Pengaruh Persepsi Kemudahan Dan Manfaat Terhadap Intensi Pembayaran Zis Melalui Platform Digital - Dina Cheetah Khairiyah; Nasution, Yenni Samri Juliati; Maidalena (JURNAL MANAJEMEN MOTIVASI, 2026)
This study is motivated by the low use of digital payments for Zakat, Infaq, and Sadaqah (ZIS) among university students. It aims to assess the quality of instruments measuring perceived ease of use, perceived usefulness, and intention to use digital ZIS through the Rasch model. A quantitative approach was applied using questionnaire data from students of the Faculty of Islamic Economics and Business, UIN Sumatera Utara, analyzed with IBM SPSS Statistics 30. The results show good model fitness, with all items valid, homogeneous, and model-appropriate. The instrument is valid and reliable. Keywords: Perceived Ease of Use, Perceived Usefulness, Intention, Digital ZIS, Rasch Model